The Role of Women in Combating the COVID-19 Outbreak in 2020–2021: A Case Study of Indonesia - Fathun, Laode Muhamad; Nathania, Vania Zahra; Wahidah, Tuhfahtu Hasanatul; Nidatya, Nurfarah; Ismira, Andi; Rai, I Nyoman Aji Suadhana (Buana Gender: Jurnal Studi Gender dan Anak, 2025)
This paper examines the role of women in addressing the spread of COVID-19 in Indonesia, employing a qualitative methodology through a case study approach. Data were collected using literature review techniques, serving as a source of secondary data. The findings indicate that key female figures—specifically the Minister of Women’s Empowerment and Child Protection (PPPA), the Minister of Social Affairs, and the Governor of East Java—played critical roles as regulators, implementers, and evaluators. As regulators, they contributed to the formulation of laws and policies; as implementers, they monitored policy enforcement and actions in the field; and as evaluators, they assessed the operational effectiveness of these policies to ensure targeted and efficient outcomes. Theoretically, these women exemplify the application of feminist values in governance, using their legitimate authority to advocate for inclusive and gender-sensitive responses to the pandemic. Their dual identities as state officials and women—who often bear the brunt of health crises—position them uniquely to understand the lived experiences of women and children. Moreover, women, particularly in the domestic sphere, serve as primary managers in preventing their households from becoming new clusters of COVID-19 transmission. When women are involved in policy-making and implementation, they are better positioned to shape interventions that directly address the needs of vulnerable populations.